(untitled) - Dauer, Victor Paul (Minneapolis, Minn., 1983)
Updated to incorporate current standards and recommendations, "the bible" of elementary P.E. continues to provide the best combination of theoretical framework and hands-on activities available. Dynamic Physical Education for Elementary School Children provides prospective teachers with the tools necessary to ensure success in today's educational environment. Whether starting a new program, restructuring an established one, or working with a team in an existing system, DPE is a valuable pre-service and in-service tool. The thirteenth edition integrates the National Standards for Physical Education and addresses new recommendations designed to increase the activity levels of children and improve their overall fitness levels.
Keywords: Physical education for children,Giáo dục tự nhiên cho trẻ; Study and teaching,Dạy và học; United States,Hoa Kỳ